A method for evaluating the retarding property of acid solution
Through long core device and three-dimensional laser scanning technology, the etching form of acid liquid in carbonate rock was analyzed, and the problem of difficulty in evaluating the slow performance of acid liquid in the existing technology was solved, and intuitive, simple and low-cost acid was achieved. The liquid slow performance evaluation was obtained, and the effective action distance and crack etching depth of acid liquid in carbonate reservoir were obtained.
Patent Information
- Application Number
- CN202411288962.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The prior art lacks a method with intuitive results, simple operation, low cost and real reaction to acid flow to evaluate the slow performance of acid liquid, and is particularly difficult to obtain the effective distance of acid liquid in carbonate reservoirs and Crack etching depth.
The long core device was used to perform the acid liquid flow etching experiment. The etching morphology data was analyzed using a three-dimensional laser scanning system, including the acid liquid action distance, crack etching width and depth, combined with the The seam width curve and seam depth curve slope were used to quantitatively evaluate the acid retarding rate.
A simple and low-cost acid slow performance evaluation was achieved. The experimental results directly reflect the flow characteristics of the acid in the core, reduce the experimental cost, and are more in line with the actual acidification process.
Smart Images

Figure CN118817683B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas field development and relates to a method for evaluating the retarding property of acid fluid. Background Art
[0002] Acidizing is one of the important measures to increase and stabilize the production of carbonate reservoirs. In order to make the acid penetrate farther in the formation and achieve the purpose of deep acidizing, the acid system used must be able to delay the H + The reaction speed with rock is called retarding performance. Retarding performance is a key indicator of acid. Accurate and effective evaluation of it is crucial for the optimization of acid formulation, design of acidizing construction parameters and successful construction. The reaction mechanism between acid and carbonate rock is very complex and there are many influencing factors. It is difficult to obtain and predict parameters such as the effective action distance and etching depth of acid during the acidizing process using purely theoretical calculation methods. The optimization of acidizing construction parameters and the evaluation of transformation effects also require the help of indoor simulation methods.
[0003] At present, there is no unified standard for the evaluation of acid retarding performance. Indoor experiments usually use acid dissolution experiments and acid-rock reaction kinetics experiments to determine parameters such as reaction rate, reaction order, and activation energy. The parameters determined by these experiments are the macroscopic results of acid-rock reactions. Acid dissolution experiments can determine the dissolution ability and reaction rate of acid on rocks. However, the acid dissolution experiment requires the dissolution rate results at different times to determine the retarding performance. The experiment itself is simple but has a long cycle, and parameters such as the effective action distance and depth of the acid cannot be obtained. The acid-rock reaction kinetics experiment can obtain the acid-rock reaction rate equation and the reaction activation energy equation. At present, the rotating rock disk device is commonly used in kinetic experiments. The device determines the reaction rate through the relative movement of the acid and the core, which is inconsistent with the flow state of the acid in the fracture during the actual acidizing process. At least four test points are required to fit the curve to obtain the reaction rate. The experimental workload is large, and the effective action distance of the acid needs to be obtained through theoretical calculation, and the acid etching depth cannot be obtained. At the same time, since the reaction process is carried out under the condition of complete excess of acid, it is impossible to directly observe the reaction characteristics of the acid during the injection into the formation.
[0004] In the prior art, the evaluation of acid retarding performance mainly relies on numerical calculations and indoor experiments. Patent CN201910611601.9 discloses a method for the distribution of conductivity of carbonate rock pre-fluid acid fracturing fractures. Patent CN201910611601.9 discloses a method for calculating the test parameters of acid etching of artificial fractures in rock slabs. Patent CN202210182027.1 discloses a method for evaluating deep acidizing retarding fluid in acid-sensitive sandstone reservoir matrix. The methods disclosed in these patents are essentially numerical calculation methods, and many calculation parameters are difficult to obtain and the calculations are complex. Patent CN202011004338.6 discloses a test method for the distribution of conductivity of acid-etched fractures, which is mainly through experiments, repeatedly displacing residual acid under two rock slabs, and fitting the distribution function of conductivity on the length of acid-etched fractures. Patent CN202010406593.7 discloses an experimental test method for the effective length of acid-etched fractures. At present, the commonly used rock plates are large in size, and it is necessary to cut the rock plates with specific size and shape requirements; two rock plates are required for each experiment to test the hydrogen ion concentration of the acid liquid, which is costly and has a long experimental cycle. Patent CN202111637781.1 discloses a method for determining the effective crack length of acid-etched sand-filled cracks under in-situ conditions. It is very difficult to obtain the underground hydraulic crack morphology of the target reservoir, and an acid fracturing simulator is required to simulate and calculate the crack length, height, and width. Patent CN202211122443.9 discloses a method for quickly evaluating the slowing performance of acid by dissolution rate. It is mainly evaluated by dissolution experiments. It is a macroscopic result and cannot evaluate the effective action distance of the acid and the crack etching depth. Patent CN201410256342.X discloses a carbonate heavy oil reservoir acidification simulation evaluation method, which obtains wormholes through acid core flow experiments, uses a three-dimensional imaging analysis system to characterize the three-dimensional digital map of the wormholes, and evaluates the acid performance and acidification effect. Patent CN202410266166.1 evaluates the deceleration effect based on CT scan images of core slices. Through computer image processing and analysis, the microstructural information inside the core is extracted. However, CT scanning is a relatively expensive experimental testing method with high cost.
[0005] Therefore, it is necessary to develop an indoor evaluation method for acid retarding performance with intuitive results, simple operation, low cost, true reflection of acid flow, and the ability to obtain acid action distance, crack etching width, and crack etching depth. Summary of the invention
[0006] The purpose of the present invention is to address the above-mentioned shortcomings and provide a method for evaluating the retarding properties of acid solution. The specific technical scheme is as follows.
[0007] Step S1, preparing a long core for slow rate evaluation;
[0008] The long core is composed of a semi-cylindrical core and a semi-cylindrical mold; the semi-cylindrical core and the semi-cylindrical mold are closed to form a complete cylindrical long core; an artificial crack is arranged on the cross section of the semi-cylindrical mold;
[0009] Step S2, performing a long core acid flow etching experiment;
[0010] An acid flow etching experiment is performed on the long core using the acid to be tested; the acid flow etching experiment is performed by a long core displacement device; the acid to be tested flows from one end of the long core to the other end of the long core through the artificial cracks on the semi-cylindrical mold, thereby achieving an etching effect of the acid to be tested on the semi-cylindrical core;
[0011] Under the same test conditions, different acid solutions to be tested are driven by the long core displacement device, and the retardation of different acid solutions to be tested can be compared; under different test conditions, the same acid solution to be tested is driven by the long core displacement device, and the influence of different test conditions on the retardation of the acid solution to be tested can be compared; the test conditions are one or more of the displacement temperature, the displacement speed, and the displacement acid volume;
[0012] Step S3, analyzing the etching morphology data of the long core after acid etching to evaluate the retarding property;
[0013] After the step S2 experiment is completed, the acid-etched surface of the semi-cylindrical core is scanned by a three-dimensional laser scanning system to obtain point cloud data of the acid-etched surface of the semi-cylindrical core, and the point cloud data is analyzed to obtain etching morphology data to evaluate the slowness of the acid to be tested.
[0014] In the above step S1, the length of the long core is set to 180-300 mm; the diameter of the long core is set to 250-260 mm.
[0015] The semi-cylindrical mold material in the above step S1 is one of polytetrafluoroethylene and Hastelloy steel; 1 to 2 artificial cracks are set on the cross-section of the semi-cylindrical mold; the width of a single artificial crack is 1 to 4 mm, the depth of a single artificial crack is 1 to 2 mm, and the artificial crack runs from one end of the semi-cylindrical mold cross-section to the other end of the semi-cylindrical mold.
[0016] The acid solution to be tested in the above step S2 is one or more acid solution systems for acidizing carbonate reservoirs.
[0017] The etching morphology data in the above step S3 includes the acid action distance, the crack etching width, the crack etching depth, the slope of the crack width curve, the slope of the crack depth curve, the crack width inflection point, and the crack depth inflection point.
[0018] The etching morphology data analysis in the above step S3 includes the following steps:
[0019] Step S3-1: The point cloud data of the semi-cylindrical core acid-etched surface is pre-processed by point cloud data processing software, including reconstruction, clipping, smoothing, repairing, and calibration of data points. During the calibration process, set x The positive direction of the axis is the flow direction. z The positive direction of the axis is the normal direction of the semi-cylindrical core acid-etched surface, and the etched fracture data volume is obtained; the three-dimensional coordinates of all the point cloud data in the etched fracture data volume are derived ( x , y , z );
[0020] Step S3-2: Using programming software, x min arrive x max The coordinate range, that is, the range from the acid inlet to the acid outlet of the semi-cylindrical core, is divided into n The step length is Δ x The unit, Δ x =( x max - x min ) / n , n is a positive integer; first obtain x min arrive( x min +Δ x ) y Maximum value of coordinates y max , y Minimum value of coordinates y min , z Maximum value of coordinates z max , z Minimum value of coordinates z min ; x min arrive( x min +Δ x ) in the range of the crack etching width is equal to ( y max - y min ), the crack etching depth is equal to ( z max - z min) absolute value; similarly, we can obtain ( x min +Δ x )arrive( x min +2Δ x ) range; repeat the above steps to obtain ( x min +( n -1)Δ x )arrive( x min + n Δ x ) within the range of the crack etching width and the crack etching depth; x min 、( x min +Δ x )、( x min +2Δ x )、…、( x min + n Δ x ) is the horizontal coordinate, with the horizontal coordinate in Δ x The crack etching width and the crack etching depth obtained within the range are taken as the ordinates, and the crack width curve and the crack depth curve of the crack etching width and the crack etching depth as the horizontal coordinates change are plotted respectively; the crack width curve and the crack depth curve are respectively intuitive reflections of the changing trends of the crack etching width and the crack etching depth along the flow direction; the crack width curve and the crack depth curve are linearly fitted to obtain the slope of the crack width curve and the slope of the crack depth curve respectively, and the retarding property of the acid solution to be tested is quantitatively evaluated through the evaluation standards of the crack width curve slope and the crack depth curve slope;
[0021] The evaluation criteria for the slope of the seam width curve are:
[0022] The seam width curve does not have the seam width inflection point, the slope of the seam width curve is less than 0, and there is no slowdown;
[0023] The slit width curve has the slit width inflection point x w The slope of the slit width curve is at the slit width inflection point. x w Before is greater than 0, at the inflection point of the slit width x w After that, it is less than 0, which means that there is a slow speed; that is, within the range from the acid inlet to the acid outlet of the rock plate surface, the crack etching width has a maximum value w max ; wmax Corresponding x coordinate x w is the inflection point of the slit width. By comparing x w The size of the acid to be tested is used to quantitatively evaluate the retarding property of the acid to be tested;
[0024] The evaluation standard of the seam depth curve slope is:
[0025] The seam depth curve does not have the seam depth inflection point, the slope of the seam depth curve is less than 0, and there is no slowdown;
[0026] The seam depth curve has the seam depth inflection point x h The slope of the seam depth curve is at the seam depth inflection point. x h Before is greater than 0, at the inflection point of the seam depth x w After that, it is less than 0, which means that there is a slow speed; that is, within the range from the acid inlet to the acid outlet of the rock plate surface, the crack etching depth has a maximum value. h max ; h max Corresponding x coordinate x h That is the inflection point of the seam depth. By comparing x h The size of the acid to be tested is used to quantitatively evaluate the retarding property of the acid to be tested;
[0027] Step S3-3, calculating the acid action distance, comprises the following steps:
[0028] When the crack width curve does not have the crack width inflection point, the acid action distance is the distance corresponding to the crack etching depth in the flow direction. x The maximum value of the coordinates;
[0029] When the seam width curve has the seam width inflection point, the acid action distance is ( x w + x h ) / 2.
[0030] The present invention discloses a method for evaluating the slowness of acid solution. Figure 1 shown.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The evaluation method of the present invention is simple and easy to operate, and the experimental results directly reflect the retarding performance of the acid solution.
[0033] 2. Carbonate rocks are generally dense. In indoor experiments, the acid cannot flow effectively in dense cores, and the acid-rock reaction produces CO2 bubbles to form a two-phase flow, which increases the flow resistance. In the present invention, a semi-cylindrical mold with artificial cracks is provided in the long core, which is conducive to the flow of acid in the core. The experiment is simple, and an additional effect is that only half a core is needed to do an experiment, reducing the experimental cost.
[0034] 3. The semi-cylindrical mold can be processed according to experimental requirements (such as the number, width, and depth of cracks). The processing is simple and can be reused after one processing.
[0035] 4. In the acid-rock reaction kinetics experiment, the core is usually rotated, and the acid leaves a spiral etching surface on the end face of the core, which is inconsistent with the process of acid flowing from the wellbore to the deep formation during the actual acidizing process. In the present invention, the acid flows from the semi-cylindrical core inlet to the distal end, which is consistent with the actual formation acid flow direction and state.
[0036] 5. In the present invention, the slowness is directly determined by etching morphological data including acid action distance, crack etching width, crack etching depth, crack width curve slope, crack depth curve slope, crack width inflection point, and crack depth inflection point. These data are simple, easy to calculate, and easy to compare.
[0037] 6. When studying the effect of a factor on the acid retarding performance, only one set of experiments is needed to determine the etching morphology data, thus reducing the experimental cost.
[0038] 7. The present invention qualitatively and quantitatively characterizes the acid liquid retarding performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flow chart of a method for evaluating the retarding property of acid solution;
[0040] Figure 2 This is a semi-cylinder mold diagram with one artificial crack;
[0041] Figure 3 This is a diagram of a semi-cylinder mold with two artificial cracks;
[0042] Figure 4 It is a semi-cylindrical core map;
[0043] Figure 5 is the seam width curve;
[0044] Figure 6 This is a seam depth curve. DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with the accompanying drawings and specific examples.
[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] The acid flow etching experiment in the embodiment is carried out by a long core displacement device, and the operation process is carried out in accordance with the industry standard "SY / T 5886-2018 Acidizing Working Fluid Performance Evaluation Method".
[0048] The programming software in the embodiment is Python 3.9.
[0049] In the embodiment, the semi-cylindrical mold is processed from polytetrafluoroethylene material. Figure 2 and Figure 3 Images of semi-cylinder molds with one artificial crack and two artificial cracks are shown respectively.
[0050] In the embodiment, the semi-cylindrical core was drilled from the limestone outcrop of the Maokou Formation. Figure 4 A half-cylinder core image is shown.
[0051] Unless otherwise specified, all chemical reagents and chemicals mentioned in the examples are commercially available.
[0052] Example 1: Step S1, preparing a long core for slow rate evaluation;
[0053] The long core is composed of a semi-cylindrical core and a semi-cylindrical mold; the semi-cylindrical core and the semi-cylindrical mold are closed to form a complete cylindrical long core; the length of the long core is 180 mm, and the diameter of the long core is 254 mm; an artificial crack with a width of 1 mm and a depth of 1 mm is set on the section of the semi-cylindrical mold; the artificial crack runs from one end of the section of the semi-cylindrical mold to the other end of the semi-cylindrical mold;
[0054] Step S2, performing a long core acid flow etching experiment;
[0055] An acid flow etching experiment was performed on the long core in step S1 using 15wt% HCl acid solution; the acid flow etching experiment was performed using a long core displacement device; the displacement speed was 1mL / min, the displacement acid volume was 200mL, and the displacement temperature was 120°C;
[0056] Step S3, analyzing the etching morphology data of the long core after acid etching to evaluate the retarding property;
[0057] After the step S2 experiment is completed, the acid-etched surface of the semi-cylindrical core is scanned with a three-dimensional laser scanning system to obtain point cloud data of the acid-etched surface of the semi-cylindrical core, and the point cloud data of the acid-etched surface of the semi-cylindrical core is analyzed to obtain etching morphological data, including acid action distance, crack etching width, crack etching depth, crack width curve slope, crack depth curve slope, crack width inflection point, and crack depth inflection point.
[0058] Example 2: Step S1, preparing a long core for slow rate evaluation;
[0059] The long core is composed of a semi-cylindrical core and a semi-cylindrical mold; the semi-cylindrical core and the semi-cylindrical mold are closed to form a complete cylindrical long core; the length of the long core is 180 mm, and the diameter of the long core is 254 mm; an artificial crack with a width of 1 mm and a depth of 1 mm is set on the section of the semi-cylindrical mold; the artificial crack runs from one end of the section of the semi-cylindrical mold to the other end of the semi-cylindrical mold;
[0060] Step S2, performing a long core acid flow etching experiment;
[0061] The long core in step S1 is subjected to an acid flow etching experiment using a gelled acid solution; the acid flow etching experiment is performed using a long core displacement device; the gelled acid formula is 15wt% HCl+1% gelling agent, the displacement speed is 1mL / min, the displacement acid volume is 200mL, and the displacement temperature is 120°C;
[0062] Step S3, analyzing the etching morphology data of the long core after acid etching to evaluate the retarding property;
[0063] After the step S2 experiment is completed, the acid-etched surface of the semi-cylindrical core is scanned with a three-dimensional laser scanning system to obtain point cloud data of the acid-etched surface of the semi-cylindrical core, and the point cloud data of the acid-etched surface of the semi-cylindrical core is analyzed to obtain etching morphological data, including acid action distance, crack etching width, crack etching depth, crack width curve slope, crack depth curve slope, crack width inflection point, and crack depth inflection point.
[0064] Example 3: Step S1, preparing a long core for slow rate evaluation;
[0065] The long core is composed of a semi-cylindrical core and a semi-cylindrical mold; the semi-cylindrical core and the semi-cylindrical mold are closed to form a complete cylindrical long core; the length of the long core is 300 mm, and the diameter of the long core is 254 mm; an artificial crack with a width of 1 mm and a depth of 1 mm is set on the section of the semi-cylindrical mold; the artificial crack runs from one end of the section of the semi-cylindrical mold to the other end of the semi-cylindrical mold;
[0066] Step S2, performing a long core acid flow etching experiment;
[0067] The long core in step S1 is subjected to an acid flow etching experiment using a gelled acid solution; the acid flow etching experiment is performed using a long core displacement device; the gelled acid formula is 15wt% HCl+1% gelling agent, the displacement speed is 3mL / min, the displacement acid volume is 200mL, and the displacement temperature is 120°C;
[0068] Step S3, analyzing the etching morphology data of the long core after acid etching to evaluate the retarding property;
[0069] After the step S2 experiment is completed, the acid-etched surface of the semi-cylindrical core is scanned with a three-dimensional laser scanning system to obtain point cloud data of the acid-etched surface of the semi-cylindrical core, and the point cloud data of the acid-etched surface of the semi-cylindrical core is analyzed to obtain etching morphological data, including acid action distance, crack etching width, crack etching depth, crack width curve slope, crack depth curve slope, crack width inflection point, and crack depth inflection point.
[0070] Example 4: Step S1, preparing a long core for slow rate evaluation;
[0071] The long core is composed of a semi-cylindrical core and a semi-cylindrical mold; the semi-cylindrical core and the semi-cylindrical mold are closed to form a complete cylindrical long core; the length of the long core is 300 mm, and the diameter of the long core is 254 mm; an artificial crack with a width of 1 mm and a depth of 1 mm is set on the section of the semi-cylindrical mold; the artificial crack runs from one end of the section of the semi-cylindrical mold to the other end of the semi-cylindrical mold;
[0072] Step S2, performing a long core acid flow etching experiment;
[0073] An acid flow etching experiment was performed on the long core in step S1 using 13wt% acetic acid solution; the acid flow etching experiment was performed using a long core displacement device; the displacement speed was 3mL / min, the displacement acid volume was 200mL, and the displacement temperature was 120°C;
[0074] Step S3, analyzing the etching morphology data of the long core after acid etching to evaluate the retarding property;
[0075] After the step S2 experiment is completed, the acid-etched surface of the semi-cylindrical core is scanned with a three-dimensional laser scanning system to obtain point cloud data of the acid-etched surface of the semi-cylindrical core, and the point cloud data of the acid-etched surface of the semi-cylindrical core is analyzed to obtain etching morphological data, including acid action distance, crack etching width, crack etching depth, crack width curve slope, crack depth curve slope, crack width inflection point, and crack depth inflection point.
[0076] Table 1 is the test results of the above Examples 1 to 4. Figure 5 is the seam width curve, Figure 6 This is a seam depth curve.
[0077] Table 1 Test results
[0078] category Slope of seam width curve Slope of seam depth curve Seam width inflection point (mm) Seam depth inflection point (mm) Acid action distance (mm) Example 1 <0 <0 / / 97.2 Example 2 First > 0, then < 0 First > 0, then < 0 158.5 160.4 159.5 Example 3 First > 0, then < 0 First > 0, then < 0 269.1 267.7 268.4 Example 4 First > 0, then < 0 First > 0, then < 0 210.6 209.6 210.1
[0079] As shown in Table 1, in Example 1, the 15wt% HCl acid solution has poor retarding property and a short effective action distance (the acid solution action distance is 97.2 mm). Figure 5 and Figure 6 The crack etching depth at the inlet end of the semi-cylindrical core acid etching surface of Example 1 is the deepest and the crack etching width is the widest, which is manifested as a reaction in the near-wellbore area of the reservoir. Compared with Example 1, Example 2 shows that the gelled acid solution in Example 2 has good retarding property and a long acid action distance (159.5 mm). The crack etching width of the semi-cylindrical core acid etching surface is the widest at the crack width inflection point, and the crack etching depth is the deepest at the crack depth inflection point, which is manifested as a reaction in the deep part of the reservoir. Compared with Example 4, Example 3 shows that the 13wt% acetic acid solution in Example 4 has a poor retarding property compared with the gelled acid solution in Example 3. The acid action distance of Example 4 is 210.1 mm, which is less than the acid action distance of Example 3, which is 268.4 mm.
[0080] In addition, the comparison between Example 2 and Example 3 illustrates the effect of displacement speed on the action distance of the acid solution. The greater the displacement speed, the smaller the crack etching depth becomes, but the crack etching width becomes larger. This shows that the increase in displacement speed will accelerate the acid-rock reaction speed.
[0081] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for evaluating the slowness of acid solution, characterized in that: The following steps are involved: Step S1, preparing a long core for slow rate evaluation; The long core is composed of a semi-cylindrical core and a semi-cylindrical mold; the semi-cylindrical core and the semi-cylindrical mold are closed to form a complete cylindrical long core; an artificial crack is arranged on the cross section of the semi-cylindrical mold; Step S2, performing a long core acid flow etching experiment; An acid flow etching experiment is performed on the long core using the acid to be tested; the acid flow etching experiment is performed by a long core displacement device; the acid to be tested flows from one end of the long core to the other end of the long core through the artificial cracks on the semi-cylindrical mold, thereby achieving an etching effect of the acid to be tested on the semi-cylindrical core; Step S3, analyzing the etching morphology data of the long core after acid etching to evaluate the retarding property; After the step S2 experiment is completed, the acid-etched surface of the semi-cylindrical core after acid etching is scanned by a three-dimensional laser scanning system to obtain point cloud data of the acid-etched surface of the semi-cylindrical core, and the obtained point cloud data is analyzed to obtain etching morphological data to evaluate the slowness of the acid to be tested; the etching morphological data includes acid action distance, crack etching width, crack etching depth, crack width curve slope, crack depth curve slope, crack width inflection point, crack depth inflection point; The etching morphology data analysis in step S3 comprises the following steps: Step S3-1, pre-processing the acquired point cloud data of the acid-etched surface of the semi-cylindrical core through point cloud data processing software to obtain an etched fracture data volume; exporting the three-dimensional coordinates (x, y, z) of all the point cloud data in the etched fracture data volume; Step S3-2: at x min to x max The coordinate range is divided into n units with a step size of Δx, Δx = (x max -x min ) / n, n is a positive integer; first get x min to (x min +Δx) within the range of the maximum value of the y coordinate y max , the minimum value of the y coordinate y min , the maximum value of the z coordinate z max , the minimum value of the z coordinate min ;x min to (x min The crack etching width within the range of (y max -y min ), the crack etching depth is equal to (z max -z min ) is the absolute value; similarly, we can obtain (x min +Δx) to (x min +2Δx) range; repeat the above steps to obtain (x min +(n-1)Δx) to (x min +nΔx) range of the crack etching width and the crack etching depth; x min 、(x min +Δx)、(x min +2Δx)、…、(x min +nΔx) as the horizontal coordinate, and the crack etching width and the crack etching depth obtained by the horizontal coordinate within the range of Δx as the vertical coordinate, and respectively draw the crack width curve and the crack depth curve of the crack etching width and the crack etching depth as the x-axis coordinate changes; the crack width curve and the crack depth curve are respectively intuitive reflections of the change trends of the crack etching width and the crack etching depth along the flow direction; linear fitting is performed on the crack width curve and the crack depth curve to obtain the slope of the crack width curve and the slope of the crack depth curve, respectively, and the retarding property of the acid to be tested is quantitatively evaluated through the evaluation standards of the crack width curve slope and the crack depth curve slope; The evaluation criteria for the slope of the seam width curve are: The seam width curve does not have the seam width inflection point, the slope of the seam width curve is less than 0, and there is no slowdown; The slit width curve has the slit width inflection point x w The slope of the slit width curve is at the slit width inflection point x w Before it is greater than 0, at the inflection point of the slit width x w After that, it is less than 0, which means that there is slowness; that is, within the range from the acid inlet to the acid outlet of the rock plate surface, the crack etching width has a maximum value w max ;w max The corresponding x coordinate x w That is the inflection point of the slit width. By comparing x w The size of the acid to be tested is used to quantitatively evaluate the retarding property of the acid to be tested; The evaluation standard of the seam depth curve slope is: The seam depth curve does not have the seam depth inflection point, the slope of the seam depth curve is less than 0, and there is no slowdown; The seam depth curve has the seam depth inflection point x h The slope of the seam depth curve is at the seam depth inflection point x h Before is greater than 0, at the inflection point x of the seam depth w After that, it is less than 0, which means that there is slowness; that is, within the range from the acid inlet to the acid outlet of the rock plate surface, the crack etching depth has a maximum value h max ;h max The corresponding x coordinate x h That is the inflection point of the seam depth. By comparing x h The size of the acid to be tested is used to quantitatively evaluate the retarding property of the acid to be tested; Step S3-3, calculating the acid action distance, comprises the following steps: When the crack width curve does not have the crack width inflection point, the acid liquid action distance is the maximum value of the x-coordinate corresponding to the crack etching depth in the flow direction; When the seam width curve has the seam width inflection point, the acid action distance is (x w +x h ) / 2.
2. The method for evaluating the slowness of acid solution according to claim 1, characterized in that: In step S1, the length of the long core is set to 180-300 mm; the diameter of the long core is set to 250-260 mm.
3. The method for evaluating the slowness of acid solution according to claim 1, characterized in that: The semi-cylindrical mold material in step S1 is one of polytetrafluoroethylene and Hastelloy steel; 1 to 2 artificial cracks are set on the cross-section of the semi-cylindrical mold, the width of a single artificial crack is 1 to 4 mm, the depth of a single artificial crack is 1 to 2 mm, and the artificial crack runs from one end of the semi-cylindrical mold cross-section to the other end of the semi-cylindrical mold.
4. The method for evaluating the slowness of acid solution according to claim 1, characterized in that: The acid solution to be tested in step S2 is one or more acid solution systems for acidizing carbonate reservoirs.
Citation Information
Patent Citations
Method for predicting pad-acid-fracturing crack flow conductivity distribution of carbonate rock
CN110397430A
Acid etching crack flow conductivity distribution testing method
CN112345436A
Experimental test method for effective length of acid etching crack
CN113671148A
Method for determining effective fracture length of acid etching sand-packed fracture under in-situ condition
CN114278266A
Evaluation device and method for retarding effect and plug removal performance of plug removal liquid
CN118130455A
